Sosialisasi dan Pelatihan Pelaksanaan Operasional Homestay di Dusun Terbang, Desa Cibiru Wetan - Gafrilia Prianka, Winda; Syakib Asqalani Rifai, Muhammad; Nurul Aini, Revina (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Cibiru Wetan Village in Cileunyi Sub-district, Bandung Regency, West Java, has achieved achievements at the local, national and ASEAN levels. The success of this village cannot be separated from the idea of economic development, especially in the field of digitalization and tourism. The Dusun Terbang homestay in Dusun 01 RW 02 is a major discovery. The homestay helps maintain local culture by providing income for the community and attracting tourists with welcoming dances. This homestay has attracted tourists since 2022 and can promote rural tourism. Homestay management has improved, but operational management, welcoming guests, cleanliness, and security still need to be improved. With the socialization and training methods provided through workshop activities to the community and producing scientific updates on homestay management in Dusun Terbang, the average value of the workshop reached 70%, which indicates an increase in understanding and competence in topics related to the workshop, so that community-based homestay development can improve the tourism economy. Sustainable tourism can also be achieved through community homestay development. The socialization and training activities of this workshop have increased the understanding of homestay development and operational management.